ALGORITHMIZATION OF HARMONIZATION FOR PROCESSES OF INDUSTRIAL AND TRADE POLICIES BASED ON ECONOMIC SECURITY OF THE REGION - Ajshat Baichorova; Olga Boris (Вестник Северо-Кавказского федерального университета)
This article deals with the harmonization of trade and industrial policies of economic systems based on economic security, the algorithm is offered for harmonization of industrial and commercial policy of economic systems.